Young adults’ experiences of dental anxiety: a multidisciplinary qualitative study of triggers, avoidance, and intervention strategies - Ab Malek, Azizi; Mohd Radzi, Nawwal Alwani; Che Musa, Muhd Firdaus (Elsevier, 2025)
Dental anxiety is a clinically significant condition that shares core features with specific phobia, including anticipatory fear, autonomic arousal, and behavioral avoidance. Particularly prevalent among young adults, dental anxiety contributes to delayed treatment, deteriorating oral health, and psychological distress. Despite various intervention efforts, limited research has examined the emotional, cognitive, and contextual factors underlying dental anxiety through a multidisciplinary lens. This qualitative study explored the lived experiences and clinical insights of young adults, dentists, and mental health professionals in managing dental anxiety. Using Braun and Clarke’s reflexive thematic analysis, data from focus group discussions with 18 dentists and in-depth interviews with 16 high-anxiety young adults (MDAS ≥ 19) and 4 mental health professionals (clinical psychologists and psychiatrists) were inductively analyzed with NVivo software. Ten interrelated themes emerged across five core domains: (1) psychological mechanisms including autonomic symptoms and anxiety-driven behaviors; (2) trauma-related conditioning rooted in early dental experiences; (3) cognitive-affective patterns shaped by trust, fear of the unknown, and perceived control; (4) intervention preferences emphasizing visual tools and empathic delivery; and (5) behavioral and systemic outcomes such as treatment avoidance and increased resource demands. Findings support trauma-informed, multidisciplinary care models incorporating early screening, sensory-adapted environments, and structured psychoeducation. Dental anxiety should be reframed within broader mental health frameworks to enhance psychological safety, improve engagement and reduce long-term burden.